Foreign Ownership Shares and Trade Propensity in Indonesian Edible Oil, Vegetable and Animal Fats Industry - Dahlia Nauly (Signifikan: Jurnal Ilmu Ekonomi, 2022)
Presidential Regulation (Perpres) No 44/2016 states that in the vegetable and animal crude oil industry, copra industry, coconut oil industry, palm oil industry, foreign ownership is limited at a maximum of 95 percent. These industries are included in the edible oil, vegetable and animal fats industry (ISIC 104). This study analyzes the effect of foreign ownership share on the trade propensity in the edible oil, vegetable and animal fats industry in Indonesia using the Tobit model. The data used are the cross-section data from 2015 Annual Survey of the Manufacturing industry from Statistics Indonesia. The results show that firms with foreign ownership share of more than 95 percent have the same export propensity with foreign ownership of between 50 and 95 percent. However, the import propensity of firms with foreign ownership between 50 and 95 percent is the lowest compared to other ownership. The government should continue to restrict foreign ownerhip shares at the maximum of 95 percent in this industry.How to Cite:Nauly, D. (2022). Foreign Ownership Shares and Trade Propensity in Indonesian Edible Oil, Vegetable and Animal Fats Industry. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 95-106. https://doi.org/10.15408/sjie.v11i1.18408.